2015
DOI: 10.1007/s10600-015-1370-0
|View full text |Cite
|
Sign up to set email alerts
|

Cashmins A and B, Potent Antioxidant Coumarins from Sorbus cashmiriana

Abstract: Cashmins A (1) and B (2), two new coumarins, have been isolated from the chloroform-soluble subfraction of the methanolic extract of Sorbus cashmiriana Hedl. Both compounds showed potent antioxidant activity in different antioxidant assays.The genus Sorbus (Rosaceae) comprises of 200 species which are commonly grown in Asia, Africa, and South America. Out of these, seven species have so far been identified in Pakistan. One of these is Sorbus cashmiriana Hedl., which is a tree found in Kashmir and the western H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Cashmin A and cashmin B showed significant antioxidant activity in DPPH and ABTS assays. Their Fe ?3 reducing and hydrogen peroxide scavenging activities were confirmed as well (Khan et al 2015).…”
Section: Antiradical Activity In Chemical Modelsmentioning
confidence: 68%
See 1 more Smart Citation
“…Cashmin A and cashmin B showed significant antioxidant activity in DPPH and ABTS assays. Their Fe ?3 reducing and hydrogen peroxide scavenging activities were confirmed as well (Khan et al 2015).…”
Section: Antiradical Activity In Chemical Modelsmentioning
confidence: 68%
“…Asia S. cashmiriana is a tree found in Kashmir and the western Himalayas, where its bark is used in folk medicine to treat nausea and heart diseases. The berries of this plant are a remedy for scurvy (Khan et al 2015). Another Asian species-S. commixtamainly distributed in Korea, Japan and China has also a long-standing folk use.…”
Section: Medicinal Usementioning
confidence: 99%
“…The bark preparation of S . cashmiriana has been used to treat nausea and heart diseases, while its berries have been used to cure scurvy [ 15 ]. The fruits, stems and bark S .…”
Section: Botanical Classification and General Usesmentioning
confidence: 99%
“…Both compounds demonstrated outstanding antioxidant activity in H 2 O 2 (IC 50 15.4 and 18.6 μmol/mL), as well as in ABTS •+ scavenging assays (IC 50 24.4 and 18.3 μmo/mL). For comparison, IC 50 of ascorbic acid were 11.4 μmol/mL in H 2 O 2 and 6.5 μmol/mL in ABTS •+ assays [ 15 ].…”
Section: Antioxidant Potential Of Sorbus Sppmentioning
confidence: 99%
“…Berries are used to cure scurvy (Bhattacharjee, 2003;Perry, Metzger, 1980;Krishna, 1972;Jayaweera, 1982;Krachmal, 1980). Previously, six triterpenes (Kazmi et al, 2007;Kazmi et al, 2009;Kazmi et al, 2011) and two coumarins (Khan et al, 2015) have been reported by us from this species. The ethnopharmacologic and chemotaxonomic importance of the genus Sorbus prompted us to carry out further phytochemical studies on S. cashmiriana.…”
Section: Introductionmentioning
confidence: 57%